1981
DOI: 10.1210/endo-108-4-1407
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Metabolizing Enzymes in Human Breast Cancer Cells. II. 5α-Reductase, 3α-Hydroxysteroid Oxidoreductase, and 17β-Hydroxysteroid Oxidor educt ase*

Abstract: Evidence that some human breast cancers can form biologically active sex steroids from extracellular precursors has prompted us to investigate several human breast cancer cell lines for similar steroidogenic capability. We have previously reported that MCF-7 and MDA-MB-231 human breast cancer cells can transform testosterone to estradiol but that aromatase activity is not apparent in the HBL-100 human breast cell line. We report here the presence of 17 beta-hydroxysteroid oxidoreductase, 5 alpha-reductase, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Activity of 5a-reductase was previously detected in human breast carcinoma cell lines (MacIndoe & Woods 1981), and 5a-reductase activity was elevated 4-8 times in breast cancer tissues compared with non-tumorous breast tissues (Wiebe et al 2000). mRNA expression of 5a-reductase type 1 was detected in all the breast carcinoma tissues examined (Suzuki et al 2001a, Lewis et al 2004, Ji et al 2004, while that of 5a-reducatase type 2 was detected in 38-100% of the tumors ( (Suzuki et al 2001a, Lewis et al 2004.…”
Section: A-reductasesmentioning
confidence: 96%
“…Activity of 5a-reductase was previously detected in human breast carcinoma cell lines (MacIndoe & Woods 1981), and 5a-reductase activity was elevated 4-8 times in breast cancer tissues compared with non-tumorous breast tissues (Wiebe et al 2000). mRNA expression of 5a-reductase type 1 was detected in all the breast carcinoma tissues examined (Suzuki et al 2001a, Lewis et al 2004, Ji et al 2004, while that of 5a-reducatase type 2 was detected in 38-100% of the tumors ( (Suzuki et al 2001a, Lewis et al 2004.…”
Section: A-reductasesmentioning
confidence: 96%
“…Moreover, the levels oftranslatable tissue-specific 5a-reductase mRNAs as monitored in the Xenopus oocytes correlated with the variable 5a-reductase activities in female rat liver, male rat liver, and prostate homogenates; the ratio of their specific activities was of 2500:630:1, respectively. Altogether, these results provide supporting evidence in favor of the transcriptional control of 5a-reductase expression in rat tissues.ical inactivation of 4-ene-3-ketosteroids, mainly adrenal corticosteroids (19).Previous biochemical studies of 5a-reductase have revealed kinetic parameters, such as affinity constants to steroid hormones, as well as the enzyme subcellular distribution in the rough endoplasmic reticulum and/or nuclei of various tissues (1,(20)(21)(22)(23)(24). Because the activity of Sareductase is extremely unstable in cell-free preparations (1, 20), it has not been purified, and therefore the regulation of its expression could not be studied at the molecular level.…”
mentioning
confidence: 58%
“…Previous biochemical studies of 5a-reductase have revealed kinetic parameters, such as affinity constants to steroid hormones, as well as the enzyme subcellular distribution in the rough endoplasmic reticulum and/or nuclei of various tissues (1,(20)(21)(22)(23)(24). Because the activity of Sareductase is extremely unstable in cell-free preparations (1, 20), it has not been purified, and therefore the regulation of its expression could not be studied at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…We now report the results of experiments which have identified and partially characterized separate cytosolic E1 and DHEA 17-ketosteroid reductase activities (17-KSR's) within MCF-7 cells, each of which appears to be different from the previously identified particulate 17-KSR that mediates the conversion of androstenedione (AE) to testosterone (T) in this cell line [18]. and have been maintained as described previously [19].…”
Section: Discussionmentioning
confidence: 94%
“…We have reported previously that MCF-7 cells also contain particulate enzyme activity that interconverts androstenedione (AE) and testosterone (T) using NADP (H) [18]. It is not yet clear whether or not NAD(H) can be utilized by this system, whether the AE/T interconversion is mediated by one or more enzymes, or whether this particulate enzyme activity is the same or different from the particulate activity which mediates the interconversion of E1 and E2.…”
Section: -Ketosteroid Reductases In Breast Cancer Cellsmentioning
confidence: 99%